Risk Management Analysis in the Waluyo Joyo Dragon Fruit Collector Business in Banyuwangi - Prakusya, Wildan Bima; Wono, Hilda Yunita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes internal risk management at Waluyo Joyo, a dragon fruit aggregation MSME in Banyuwangi, Indonesia. MSMEs are crucial to the national economy, yet they often lack formal risk management systems. Waluyo Joyo, despite having stable cash flow, faces sustainability threats due to its highly informal, owner-centric operational model, absence of Standard Operating Procedures (SOPs), and rudimentary financial recording. The research problem is how to prioritize the main risks to ensure the business's sustainability. The objective is to identify and prioritize the key internal risks managerial, operational, and financial using a qualitative case study approach. The method involved in-depth interviews with the business owner and employees, coupled with direct observation. Data were analyzed thematically and assessed based on likelihood and impact to create a risk prioritization matrix. The findings reveal that the most critical risks are managerial and operational. The lack of a formal management structure and written SOPs leads to inconsistent fruit sorting quality, communication gaps, and high dependence on volatile freelance labor. These issues directly cause financial inaccuracies and supplier dissatisfaction. The primary implication is that mitigating the foundational managerial risks is essential for improving operational stability and financial transparency. This study provides a structured framework for the owner to prioritize and address risks, offering a practical model for similar agribusiness MSMEs to enhance their resilience and long-term sustainability.